Beliefs surrounding the use of inhaled asthma medication in The Gambia: a qualitative study of asthma patients and healthcare workers - S. Jayasooriya; M. Inoue; H. Allen; M. Bojang; A. Ceesay; S. Touray; R. Cooper; K. Mortimer; J. Balen (npj Primary Care Respiratory Medicine)
Abstract Asthma-related mortality is high in low- and middle-income countries. Little is known about public perceptions of inhaled medicines. We conducted semi-structured interviews with asthma patients and healthcare workers at three secondary care facilities in The Gambia, between August and November 2022. Thematic analysis was used to interpret these data. A total of 20 patients and 15 healthcare workers were interviewed. Both groups noted limited access to inhalers was an issue resulting in continued use of oral medications. Some patients recognised the benefits of inhalers, yet beliefs that inhalers were dangerous were common. Reliance on oral short-acting beta agonists meant patients saw asthma as a recurrent acute condition resulting in an emphasis on hospital management with little awareness of inhaled preventative medicines. Increasing access to inhaled medicines has the potential to reduce costly avoidable admissions, but socio-cultural factors, in addition to medication supply, need addressing.